Algal biochar mediated detoxification of plant biomass hydrolysate: Mechanism study and valorization into polyhydroxyalkanoates. (February 2023) - Bhatia, Shashi Kant; Gurav, Ranjit; Cho, Do-Hyun; Kim, Byungchan; Jung, Hee Ju; Kim, Su Hyun; Choi, Tae-Rim; Kim, Hyun-Joong; Yang, Yung-Hun
Graphical abstract: Highlights: Lignocellulosic biomass pretreatment leads to the production of various side products. Eucheuma spinosum biochar (EB-BC 600) is specific to phenolics removal. Furfural and HMF adsorption follow the pseudo-first-order of kinetics. Furfural and HMF adsorption follow the Langmuir isotherm model. The use of detoxified hydrolysates leads to high biomass and PHA production. Abstract: In this study, fourteen types of biochar produced using seven biomasses at temperatures 300 °C and 600 °C were screened for phenolics (furfural and hydroxymethylfurfural (HMF)) removal. Eucheuma spinosum biochar (EB-BC 600) showed higher adsorption capacity to furfural (258.94 ± 3.2 mg/g) and HMF (222.81 ± 2.3 mg/g). Adsorption kinetics and isotherm experiments interpreted that EB-BC 600 biochar followed the pseudo-first-order kinetic and Langmuir isotherm model for both furfural and HMF adsorption. Different hydrolysates were detoxified using EB-BC 600 biochar and used as feedstock for engineered Escherichia coli. An increased polyhydroxyalkanoates (PHA) production with detoxified barley biomass hydrolysate (DBBH: 1.71 ± 0.07 g PHA/L), detoxified miscanthus biomass hydrolysate (DMBH: 0.87 ± 0.03 g PHA/L) and detoxified pine biomass hydrolysate (DPBH: 1.28 ± 0.03 g PHA/L) was recorded, which was 2.8, 6.4 and 3.4 folds high as compared to undetoxified hydrolysates. This study reports the mechanism involved in furfural and HMF removal using biochar and valorization of hydrolysate into PHA.